Enhancement of Thrombin-Induced Degradation of Phosphatidylcholine in Reserpinized Rabbit Platelets - Watanabe, Yasuko; Soda, Masako; Kobayashi, Bonro (Thrombosis and Haemostasis, 1981)
When 1-14C-arachidonic acid-labeled, washed platelets from the reserpinized rabbits were exposed to thrombin, the decrease in radioactivity of phospholipids was significantly stimulated as compared with the control platelets. The increase in radioactivity of fatty acids and their oxygenated metabolites was also stimulated. TLC analysis revealed that the stimulation of the decrease in radioactivity of phospholipids was almost exclusively attributed to that of phosphatidylcholine (PC), and that thrombin induced a slight but significant increase in radioactivity of phosphatidyl ethanolamine (PE) in the reserpinized platelets. The results suggest that thrombin-induced degradation of PC is enhanced in the reserpinized platelets, and the overproduced fatty acids would be metabolized to the larger amount of oxygenated products which result in the activation of the platelets. Thrombin-induced mobilization of PC to PE in the reserpinized platelet phospholipids was also suggested.
Keywords: Platelet phospholipids; Reserpine; Thrombin